Presenting - Pincus, Aileen (London, United Kingdom : Dorling Kindersley Limited, 2022)
A new and updated edition of DK's practical guide to presenting. The practical guide that gives you the skills to improve your presentation skills. Find out how to improve your presentation skills by learning how to prepare properly, capture attention, speak confidently and deliver your message. You'll discover how to structure your presentation, engage with your audience and make an impact. In a slim, portable format, Essential Managers- Presenting gives you a practical "how-to" approach with step-by-step instructions, tips, checklists, and "ask yourself" features showing you how to plan your presentations, hold an audience, and make an impact. If you are keen to brush up on or enhance your presentation skills, then this is the guide for you
Chapter 1. Planning to present -- Chapter 2. Preparing and practising -- Chapter 3. Taking centre stage.
Includes index.
Keywords: BUSINESS PRESENTATIONS